Effect of Zn content on electromagnetic interference shielding effectiveness of Mg–Zn alloys. (July 2014) - Song, K.; Pan, F.; Chen, X.; Tang, A.; Pan, H.; Luo, S.
<x content-type="archive" xml:space="preserve">Abstract</x> Magnesium alloys are widely used in various fields. However, their electromagnetic interference (EMI) shielding effectiveness (SE) was rarely reported. In this work, the electrical properties and EMI SE of Mg–xZn (x = 0–5 wt-%) alloys in as-cast, T4 and T6 states were investigated. The SE value was measured in the frequency range 30–1500 MHz by the coaxial cable method at ambient temperature. With increasing content of Zn, the SE value shows variations in as-cast, T4 and T6 states. In the T6 state, Mg–4Zn alloy possesses the highest SE value of 116–95 dB in the whole test frequency range. The EMI shielding of Mg–Zn alloys has been attributed to the contributions from reflection (SER) and absorption (SEA), Zn solubility and also the quantity and distribution of second phases in the Mg–Zn matrix.